(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract. Adolescence is a complex developmental stage that represents the transition from childhood to adulthood. Over time, its conceptualization has evolved under the influence of biological discoveries, psychological theories, sociocultural changes, and educational reforms. This thesis examines the historical emergence of adolescence as a scientific concept and analyzes major theoretical perspectives that have shaped its understanding. Drawing on classical and contemporary theories, the study highlights how adolescence has been interpreted differently across historical periods and disciplinary frameworks. The paper emphasizes that adolescence is not merely a biological phase but a multidimensional construct shaped by social, cultural, and psychological factors.